Crescimento de plantas jovens de Mimosa caesalpiniifolia Benth., Caesalpinia ferrea Mart., Tabebuia aurea (Manso) Benth. & Hook., e Handroanthus impetiginosus Mattos - Pinto, José Rivanildo de Souza (Universidade Federal Rural do Semi-Árido, 2014)
Sabiá (Mimosa caesalpiniifolia), jucá (Caesalpinia férrea), craibeira (Tabebuia aurea) e ipê-roxo (Handroanthus impetiginosus) are species from the Caatinga biome, used in reforestation programes and degraded areas recuperation. Planting in the Caatinga requires some attention to traits that depend on previous knowledge of the physiological and ecological characteristics of the plants. The study of the growth of a plant under different environmental conditions offer good hints on the best conditions to cultivate it. The disponibility of light is one of these factors that affect the development of plants, with morphological and physiological changes. This work had the objective of analysing the growth of young plants of the species indiated under differente shading levels, at the Mossoro-RN municipality. The experiment was conduced at the Universidade Federal do Semiarido (UFERSA), under a complete blocks experimental design, and a factorial scheme of 4 X 4 factors, and 8 time split plots, wher the first factor are the four species, the second factor is the four shading levels (0, 30, 50 and 70%), and the time split plots are the evaluation times (0, 21, 42, 63, 84, 105, 126 and 147 day after transplanting). It was evaluated in each time: Plant height (CPA), stem diameter (DC), stem dry mass (MSC), leaves dry mass (MSF), above ground dry mass (MSPA) and leaves area (AF). With was calculated the leaf area ratio (RAF), the specific leaf area (AFE), the absolute growth rate (TCA), the relative growth rate (TCR), and the net assimilatory rate (TAL). The shading levels affected the initial growth of M. caesalpinifolia, C. ferrea, and H. impetiginosus, with the best values for the growth indicators observed at 50% shade, with higher growth rates. The reduction of light disponibility induced higher values of CPA, AF, MSF and MSPA fos M. caesalpinifolia, C. ferrea, and H. impetiginosus. T. aurea presented physiological plasticity to all the shading levels, with similar growth under full sun and shade
Growth of young plants of Mimosa caesalpiniifolia, Caesalpinia ferrea, Tabebuia aurea and Handroanthus impetiginosus under shade
Keywords: Caatinga plants; Seedlings production; Shading levels; Growth analysis; Plantas da Caatinga; Produção de mudas; Intensidade luminosa; Análise de Crescimento; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA